On The Geometric Continued Fractions in Positive Characteristic - Sana Driss; Hassen Kthiri (IndoMS, 2019)
In this paper we study another form in the field of formal power series over a finite field. If the continued fraction of a formal power seriesin F_q((X^-1)) begins with sufficiently largegeometric blocks, then f is transcendental.